Electrode material for H-type electrolytic cell and method for simultaneously degrading typical explosive-deficient / rich wastewater
By using CeO2-MnO2@CuO NWs/CF and CoS2@CC as electrode materials in H-type electrolytic cells, combined with heterogeneous electrofenton and anodizing process, the simultaneous degradation of the lack of/rich electron explosives in explosive wastewater was successfully achieved, and the problems of resource waste and environmental pollution in the existing technology were solved.
Patent Information
- Application Number
- CN202510221781.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-02-27
AI Technical Summary
The prior art is difficult to effectively degrade the lack of/rich explosives in explosive wastewater, and there are problems of waste of resources and environmental pollution.
The H-type electrolytic cell is used to separate the cathode chamber and the anode chamber through a proton membrane, and CeO2-MnO2@CuO NWs/CF is used as the cathode material and CoS2@CC is used as the anode material, combining heterogeneous electrofenton and anodic oxidation process to achieve simultaneous degradation of wastewater from lack of/rich electron explosives.
It has achieved efficient degradation of typical electronically deficient/rich explosive wastewater, solved the problems of resource waste and environmental pollution, and showed good application prospects.
Smart Images

Figure CN119841401A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemical materials and explosive wastewater environmental treatment, and relates to an electrode material for an H-type electrolytic cell, and specifically to a cathode material and an anode material for the H-type electrolytic cell, and a method for simultaneously degrading typical electron-deficient / rich explosive wastewater by applying the cathode material and the anode material in the H-type electrolytic cell. Background Art
[0002] Explosives are high-energy organic compounds that can be used for military and peaceful purposes, such as nuclear devices, rocket propellants, and rocket fuels. The production, transportation, and use of explosives can bring a large amount of residues to water bodies, posing a potential threat to human health and ecological security. 2,4-Dinitroanisole (DNAN), as a typical electron-rich compound, is a kind of insensitive munition used in the defense industry. Although its water solubility is very low (about 276 mg / L at room temperature), it can form rod-shaped crystals at high concentrations, which will have a significant impact on the environment when adsorbed onto clay and organic matter in the soil. At present, the methods used to remove HMX and DNAN include photocatalysis, biodegradation, etc., but all of them have the problems of long reaction time, low removal efficiency, and incomplete degradation. Therefore, exploring wastewater treatment technologies that can effectively and safely degrade explosives remains a challenging task and is also crucial for public health and environmental protection.
[0003] Electrochemical advanced oxidation processes can produce highly oxidative free radicals (such as OH) and have become a promising method for treating organic pollutants in wastewater. Among them, heterogeneous electro-Fenton (HEF) and anodic oxidation (AO) are the most representative electrochemical advanced oxidation processes. HEF generates H 2 O 2 The HEF has the advantages of easy operation and fast reaction kinetics, but the electrode may be 2 O 2 Metal sludge is generated during the production process; in addition, once the chemical oxygen demand reaches a certain removal rate, further degradation of organic matter becomes challenging, resulting in H 2 O 2Excessive consumption and waste of resources. Anodic oxidation degrades organic matter in wastewater by directly or indirectly producing ·OH through oxidation or surface catalysis of electrodes. Its limitations are high energy consumption and prolonged treatment time. It can be foreseen that if a dual degradation system combining HEF and AO can be manufactured, the complementarity of heterogeneous electro-Fenton and anodic oxidation can be achieved, and the synergistic removal of multiple pollutants can be achieved. However, the following difficulties are still faced: 1. Whether the electrodes in the two electrode chambers need to be the same. If they are the same, it is necessary to consider whether the anode material is suitable for the cathode at the same time, and whether the cathode material is suitable for the anode at the same time; if they are different, it is necessary to consider how each electrode solves the problems of HEF and AO. 2. It is necessary to solve the problems of cathode metal sludge and high energy consumption of the anode at the same time (examining cycle stability, etc.). Summary of the invention
[0004] The purpose of the present invention is to provide a cathode material and an anode material for an H-type electrolytic cell to address the safety issues such as the difficulty in treating explosive wastewater, the ability to degrade only single electron-deficient or electron-rich wastewater, and the explosion that may be caused by the explosive wastewater infiltrating into the soil, as well as the environmental pollution caused by its toxicity. The cathode material and the anode material are used as the cathode and anode of the H-type electrolytic cell respectively, and the cathode and the anode are separated by a proton membrane, so that HEF and AO are combined, and typical explosive-deficient / rich wastewater can be degraded at the same time. This not only solves the deficiency of the prior art that only a single wastewater can be degraded, but also solves the problems of environmental pollution, difficulty in degrading explosive wastewater, etc., and shows good application prospects in wastewater treatment.
[0005] The technical solution adopted by the present invention is:
[0006] An electrode material for an H-type electrolytic cell, comprising a cathode material and an anode material;
[0007] The cathode material is a copper foam immersed in NaOH and ammonium persulfate (NH 4 ) 2 S 2 O 8 ) in a mixed aqueous solution, a uniform growth of Cu(OH) 2 The copper foam with nanoneedle arrays is then grown with Cu(OH) 2 Nanoneedle arrays in copper foam immersed in Mn(NO 3 ) 2 ·4H 2 O aqueous solution, and then Ce(NO 3 ) 2 6H 2 O continues to react, and then transferred to a NaOH aqueous solution for treatment and dried to obtain a cathode material precursor, which is then calcined in an air atmosphere to obtain a cathode material (denoted as CeO 2-MnO 2 @CuO NWs / CF);
[0008] The anode material is Co(NO 3 ) 2 6H 2 O and polyvinyl pyrrolidone are added to a mixed solvent of water and ethylene glycol, and then sodium thiosulfate is added to react to obtain a precursor liquid. The activated carbon fiber cloth is placed in the precursor liquid, heat-treated at 140-160°C for 10-12 hours, cooled to room temperature, and the activated carbon fiber cloth is taken out, washed with deionized water, and dried to obtain an anode material (denoted as CoS 2 @CC).
[0009] Preferably, the cathode material is prepared by the following method: immersing the activated copper foam in a mixed aqueous solution of NaOH and ammonium persulfate for 0.5 to 1 h at room temperature, and uniformly growing Cu(OH) 2 Nanoneedle arrays were grown with Cu(OH) 2 Nanoneedle array of copper foam; Cu(OH) 2 Nanoneedle arrays in copper foam immersed in Mn(NO 3 ) 2 ·4H 2 O aqueous solution, react at 70-85°C for 0.8-1.2h, then add Ce(NO 3 ) 2 6H 2 O, 70-85°C for reaction for 0.8-1.2h, transfer the foamed copper to a NaOH aqueous solution, soak at room temperature for 30-40 minutes, take out the foamed copper, rinse with deionized water to remove surface impurities, and dry to obtain a cathode material precursor; the cathode material precursor is calcined at 300-350°C in an air atmosphere for 2-2.5h to obtain a cathode material (denoted as CeO 2 -MnO 2 @CuO NWs / CF).
[0010] The foam copper is 1cm 2 Copper foam sheet.
[0011] The activation is as follows: the foam copper is immersed in acetone, ethanol and acetic acid for 15 minutes respectively, and then washed with a large amount of deionized water until the washing liquid is neutral (pH≈7).
[0012] The NaOH and (NH 4 ) 2 S 2 O 8 In the mixed aqueous solution, the concentration of NaOH is 2-2.5 mol / L, (NH 4 )2 S 2 O 8 The concentration is 0.10~0.16mol / L.
[0013] Preferably, the NaOH and (NH 4 ) 2 S 2 O 8 In the mixed aqueous solution, the concentration of NaOH is 2.5 mol / L, (NH 4 ) 2 S 2 O 8 The concentration is 0.13 mol / L.
[0014] Preferably, at room temperature, the activated copper foam is immersed in a mixed aqueous solution of NaOH and ammonium persulfate for 0.5 to 1 h, taken out, and dried at 60° C. for 10 hours to obtain a Cu(OH) foam having grown thereon. 2 Nanoneedle arrays on copper foam.
[0015] The Mn(NO 3 ) 2 ·4H 2 The concentration of the aqueous solution of Mn(NO) is 0.1-0.166 mol / L; 3 ) 2 ·4H 2 O and Ce(NO 3 ) 2 6H 2 The molar ratio of O is 1:3 to 3:3, preferably 2:3.
[0016] Preferably, the copper foam is taken out, rinsed with deionized water, and dried at 50-70° C. for 8-12 hours to obtain a cathode material precursor.
[0017] Preferably, the cathode material precursor is heated in air at a rate of 2.5 to 3.5 °C min -1 The temperature is raised to 300-350° C., and calcined at 300-350° C. for 2-2.5 hours to obtain a cathode material.
[0018] Preferably, the anode material is prepared by the following method: Co(NO 3 ) 2 6H 2O and polyvinyl pyrrolidone are added to a mixed solvent of ethylene glycol, mixed evenly, sodium thiosulfate is added, reacted at room temperature for 1.5 to 2 hours, and ultrasonically treated for 30 to 40 minutes to obtain a dispersion; an activated carbon fiber cloth is immersed in the dispersion, heat treated at 140 to 160°C for 12 hours, the activated carbon fiber cloth is taken out, washed with deionized water, and dried at 50 to 70°C for 8 to 12 hours to obtain an anode material (denoted as CoS 2 @CC).
[0019] The Co(NO 3 ) 2 6H 2 The mass ratio of O to polyvinyl pyrrolidone is 0.95:1 to 1:1, preferably 0.97:1.
[0020] The Co(NO 3 ) 2 6H 2 The dosage ratio of O and water is 1:30-1:35 g / mL.
[0021] The volume ratio of water to ethylene glycol is 1:1.
[0022] The Co(NO 3 ) 2 6H 2 The molar ratio of O to sodium thiosulfate is 0.5:1 to 0.55:1.
[0023] The area of the activated carbon fiber cloth is 1cm 2 .
[0024] Another object of the present invention is to provide a method for simultaneously degrading typical explosive-deficient / rich wastewater, comprising: using an H-type electrolytic cell, separating the cathode chamber and the anode chamber by a proton membrane, adding an electron-deficient organic pollutant aqueous solution to the cathode chamber, adding an electron-rich organic pollutant aqueous solution and peroxymonosulfate to the anode chamber, and respectively using the cathode material (CeO 2 -MnO 2 @CuO NWs / CF) and the anode material (CoS 2 @CC) as cathode and anode, with SO 4 2- , HCO 3 - , Cl - 、NO 3 - or HPO 4 2- It is an electrolyte that can simultaneously degrade electron-deficient organic pollutants and electron-rich organic pollutants under the action of an external current.
[0025] The area of the cathode is 1 cm2 The area of the anode is 1cm 2 ; The applied current density is 5 to 20 mA, preferably 10 to 15 mA, and most preferably 10 mA.
[0026] The initial pH of the electron-deficient organic pollutant aqueous solution in the cathode chamber is 3-11, preferably 5-7, and more preferably 5; the initial pH of the electron-rich organic pollutant aqueous solution in the anode chamber is 3-11, preferably 7-11, and more preferably 9.
[0027] The peroxymonosulfate (2KHSO 5 ·KHSO 4 ·K 2 SO 4 , also known as PMS) has a final concentration of 20-25 mg / L, and permonosulfate is used as an auxiliary activator for the anode material.
[0028] The concentration of the electrolyte is 0.050-0.055 mol / L.
[0029] Preferably, the electrolyte is SO 4 2- or NO 3 - .
[0030] Most preferably, the electrolyte is SO 4 2- .
[0031] The concentration of the electron-deficient organic pollutant aqueous solution is 6-20 mg / L, and the concentration of the electron-rich organic pollutant aqueous solution is 10-60 mg / L.
[0032] The electron-deficient organic pollutant is at least one of tetramethylene tetranitramine (HMX), cyclotrimethylene trinitramine (RDX) and hexanitrohexaazaisowurtzitane (CL-20).
[0033] The electron-rich organic pollutants are trinitrotoluene (TNT), disodium azotetrazolyl (Na 2 At least one of AzTz), 3-nitro-1,2,4-triazol-5-one (NTO) and nitroguanidine (NQ).
[0034] The method for simultaneously degrading typical explosives-deficient / rich wastewater described in the present invention also includes: when power is turned on, under the action of the proton membrane, hydrogen ions in the anode chamber are transmitted to the cathode chamber, the pH values of the cathode chamber and the anode chamber are balanced, the generation of free radicals is maximized, and the organic pollutants in the two polar regions are rapidly and efficiently degraded.
[0035] Beneficial effects of the present invention:
[0036] The present invention combines the heterogeneous electro-Fenton (HEF) system with the anodic oxidation (AO) system, wherein the HEF corresponds to the cathode chamber and the AO corresponds to the anode chamber, and can simultaneously degrade electron-deficient explosives such as HMX and electron-rich explosives such as DNAN. 2 -MnO 2 @CuO / CF as cathode material enhanced interfacial charge transfer and charge carrier mobility, enhanced degradation rate, and exhibited significant redox performance. The HMX removal rate was as high as 95.1% in the HEF system. In the anode chamber, Co 2+ As a beneficial active site, the removal rate of DNAN reached 100%.
[0037] The present invention confirms that a high degradation rate is maintained in different electrolyte environments and a wide pH range; H * and 1 O 2 is the main contributor to the HEF system, while ·OH and 1 O 2 Dominant in AO system.
[0038] The present invention solves the difficulties in treating explosive wastewater, the degradation of single wastewater, the environmental pollution problems caused by safety and toxicity, provides an innovative dual degradation system for the simultaneous removal of electron-deficient / electron-rich explosives, and broadens the technical framework for treating wastewater by electrochemical advanced oxidation methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The cathode material (CeO 2 -MnO 2 @CuO NWs / CF) scanning electron microscope image and transmission electron microscope element map; a is the growth of Cu(OH) 2 Scanning electron microscopy image of copper foam with nanoneedle array; b is the scanning electron microscopy image of Mn and Ce elements in the cathode material, c is the high-resolution transmission electron microscopy image of the cathode material, d is the distribution map of all elements in the cathode material, e is the Cu element content map in the cathode material under transmission electron microscopy, f is the Mn element content map in the cathode material under transmission electron microscopy, g is the Ce element content map in the cathode material under transmission electron microscopy, h is the O element content map in the cathode material under transmission electron microscopy, i is the CuO and MnO under high-resolution electron microscopy 2 Diagram of the heterojunction formed at the interface.
[0040] Figure 2 Anode material (CoS 2@CC) scanning electron microscope image and transmission electron microscope element map; a is the scanning electron microscope image of the anode material (scale 5μm), b is the scanning electron microscope image of the anode material (scale 50nm), c is the CoS 2 d is the lattice image of the anode material under transmission electron microscopy, e is the S element content image of the anode material under transmission electron microscopy, and f is the O element content image of the anode material under transmission electron microscopy.
[0041] Figure 3 It is the degradation effect of cathode materials prepared with different molar ratios of Mn and Ce on HMX.
[0042] Figure 4 Linear voltammetric curves (a) and impedance diagrams (b) of different cathode materials.
[0043] Figure 5 The linear voltammetric curves (a) and impedance diagrams (b) of different anode materials; where C represents activated carbon fiber cloth.
[0044] Figure 6 CeO 2 -MnO 2 @Diagram of electron transfer mechanism of CuO NWs / CF heterojunction.
[0045] Figure 7 is the degradation effect of applied current density on HMX and DNAN.
[0046] Figure 8 The effects of initial pH of HMX solution (a), initial pH of DNAN solution (b) and anions (c) on degradation.
[0047] Fig. 9 It is a pathway diagram that simulates the production of free radicals by catalytic reactions in actual degradation pathways.
[0048] Fig.10 The free radicals generated during the cathode degradation of HMX are detected; a is the capture diagram of H* and ·OH during the reaction, b is the capture diagram of free radicals at different reaction times, and c is the capture diagram of free radicals during the reaction. 1 O 2 Capture image of .
[0049] Fig.11 is the free radical detected during the anodic degradation of DNAN; where a is the free radicals generated during the reaction. 2 · - and SO 4 ·- The capture diagram of b is during the reaction process. 1 O 2 Capture image of .
[0050] Fig.12 It is a diagram showing the degradation effects of other electron-deficient and electron-rich organic pollutants; wherein, a is a comparison diagram of the degradation effects of electron-deficient organic pollutants and the removal rate of total organic carbon, and b is a comparison diagram of the degradation effects of electron-rich organic pollutants and the removal rate of total organic carbon.
[0051] Fig.13 This is a test chart of the cycle stability of cathode and anode materials. DETAILED DESCRIPTION
[0052] The technical solution of the present invention is described in detail below in conjunction with specific implementation methods.
[0053] Example 1
[0054] Preparation of cathode material: The copper foam was cut into thin slices (1 cm long, 1 cm wide, and 0.1 cm thick), and soaked in acetone, ethanol, and acetic acid for 15 min, respectively, and then washed with deionized water until the pH of the washing solution was ≈ 7. At room temperature, the activated copper foam was stirred in NaOH and (NH 4 ) 2 S 2 O 8 The mixed solution (prepared with deionized water, NaOH concentration of 2.5 mol / L, (NH 4 ) 2 S 2 O 8 The concentration was 0.13 mol / L) and then immersed in water for 0.5 h to uniformly grow Cu(OH) on the copper foam. 2 The nanoneedle array was taken out and dried at 60°C for 10 hours to obtain a Cu(OH) 2 Copper foam with nanoneedle arrays. Under slow magnetic stirring, the Cu(OH) 2 The copper foam of the nanoneedle array was immersed in 0.133 mol / L Mn(NO 3 ) 2 ·4H 2 O aqueous solution, react at 80℃ for 1h, then add Ce(NO 3 ) 2 6H 2 O to a final concentration of 0.2 mol / L (the molar ratio of Mn to Ce is about 2:3), and react at 80 °C for 1 h; the resulting solid was transferred to an aqueous solution of 1 mol / L NaOH, reacted at room temperature for 30 min, the electrode sheet was taken out with tweezers, the sample was rinsed with deionized water to remove surface impurities, and dried at 60 °C for 10 h; finally, in an air atmosphere, the temperature was increased at a rate of 3 °C·min -1 The temperature was raised to 350°C and calcined at 350°C for 2 h to obtain the cathode material, which was recorded as CeO 2 -MnO 2@CuO NWs / CF.
[0055] The structural characteristics of the cathode material were investigated by scanning electron microscopy and transmission electron microscopy. Figure 1 . Figure 1 a is the growth of Cu(OH) 2 Scanning electron microscopy image of copper foam with nanoneedle arrays; Figure 1 b is a scanning electron microscope image of the cathode material with added Mn and Ce elements. It can be found that the surface of the foam copper nanoarray is covered with small particles, indicating that the Mn and Ce elements are evenly distributed on the surface of the foam copper nanoarray. Figure 1 c. Figure 1 d are the transmission electron microscopy and all element scanning images of the cathode material, Figure 1 e. Figure 1 f. Figure 1 g. Figure 1 h are the cathode materials CeO under transmission electron microscopy. 2 -MnO 2 The content of Cu, Mn, Ce, and O elements in @CuO NWs / CF shows that Mn and Ce elements are successfully loaded on the Cu surface. 2 -MnO 2 The interface between the Figure 1 i) confirmed that CeO 2 -MnO 2 @CuO NWs / CF has a heterojunction nanostructure, which also shows that the present invention will grow Cu(OH) 2 Nanoneedle arrays in copper foam immersed in Mn(NO 3 ) 2 ·4H 2 O aqueous solution, and then Ce(NO 3 ) 2 6H 2 O reaction can obtain heterojunction nanostructures, avoiding the growth of Cu(OH) 2 Nanoneedle arrays in copper foam immersed in Mn(NO 3 ) 2 ·4H 2 O and Ce(NO 3 ) 2 6H 2 O mixed aqueous solution, can only generate MnCe doped small particles, can not obtain the heterojunction morphology from the inside out.
[0056] Preparation of anode material: 0.582 g Co(NO 3 ) 2 6H 2O and 0.6 g polyvinyl pyrrolidone (average molecular weight 58000) were added to a mixed solvent of 20 mL water and 20 mL ethylene glycol. After mixing evenly, 0.62 g sodium thiosulfate was added and reacted at room temperature for 2 hours, and then ultrasonically treated for 30 minutes to fully disperse to obtain a dispersion liquid, which is the precursor liquid; the precursor liquid was transferred to a PTFE reactor, and an activated carbon fiber cloth (1 cm long, 1 cm wide, and 0.1 cm thick) was immersed in the dispersion liquid and treated at 160°C for 12 hours; cooled to room temperature, the activated carbon fiber cloth was taken out, washed with deionized water, and then dried at 60°C for 12 hours to obtain an anode material, which was marked as CoS 2 @CC.
[0057] The structural characteristics of the anode material were explored by scanning electron microscopy and transmission electron microscopy. Figure 2 . Figure 2 a- Figure 2 b is a scanning electron microscope image of the anode material. It can be seen that cobalt disulfide (CoS 2 ) nanoparticles are evenly anchored on the activated carbon fiber cloth, and the cobalt disulfide nanoparticles appear as small spherical particles with an average size of about 170nm. Figure 2 c is CoS 2 The lattice diagram of Figure 2 d. Figure 2 e are the anode materials CoS under transmission electron microscope 2 The content of Co and S elements in @CC shows that Co and S elements are successfully loaded on the surface of carbon fiber cloth; in addition, Figure 2 The disordered distribution of f oxygen confirms that no cobalt oxide is generated during the preparation of the anode material, only CoS 2 The above characterization results show that the present invention successfully prepared the anode material CoS 2 @CC.
[0058] Example 2
[0059] Degradation effect of different molar ratios of Mn and Ce on HMX
[0060] Referring to Example 1 "Preparation of cathode materials", Mn(NO 3 ) 2 ·4H 2 The concentration of O aqueous solution was 0.133 mol / L, and the Ce(NO 3 ) 2 6H 2 O was used to make the molar ratio of Mn to Ce be approximately 1:3 and 3:3 respectively. The rest was the same as in Example 1. The cathode materials obtained were denoted as CeO 2 -MnO 2 -1:3@CuO NWs / CF, CeO 2-MnO 2 -3:3@CuONWs / CF.
[0061] The cathode materials prepared with different molar ratios of Mn and Ce were used as cathodes. The CoS prepared in Example 1 2 @CC is used as anode to investigate the electrocatalytic degradation of organic pollutants:
[0062] 10 mg HMX was weighed into a 1L volumetric flask and titrated to the mark with deionized water to obtain a 10 mg / L HMX solution; 15 mg DNAN was weighed into a 1L volumetric flask and titrated to the mark with deionized water to obtain a 15 mg / L DNAN solution; 0.1 mmol / L sulfuric acid and 0.1 mmol / L sodium hydroxide were used to adjust the initial pH of the HMX solution and the DNAN solution to 7. 2 @CC) as anode (anode area is 1cm 2 ), in the cathode chamber, cathode materials prepared with different molar ratios of Mn and Ce were used as cathodes (cathode area 1 cm 2 ), the two electrode chambers were separated by N117 proton exchange membrane. 50 mL of HMX solution was placed in the cathode chamber of the H-type electrolyzer, and 50 mL of DNAN solution was placed in the anode chamber of the H-type electrolyzer. At the same time, peroxymonosulfate (2KHSO 5 ·KHSO 4 ·K 2 SO 4 , also known as PMS, final concentration 20 mg / L) as an auxiliary activator for the anode material, the cathode and anode compartment electrolytes were 0.05 mol / L Na 2 SO 4 After power on, about 2 mL of solution was taken out from the cathode chamber with a syringe every 10 min, filtered with a 0.22 μm polyethersulfone filter membrane, and quenched with 0.5 mL of methanol to remove the remaining free radicals. About 2 mL of solution was taken out from the cathode chamber with a syringe every 1 min, filtered with a 0.22 μm polyethersulfone filter membrane, and quenched with 0.5 mL of methanol to remove the remaining free radicals. The concentration of HMX was detected at 254 nm using a high performance liquid chromatography (HPLC) UV-visible detector, and the concentration of DNAN was detected at 280 nm. The reverse phase chromatographic column C18 column (5 μm, 4.6 mm × 250 mm) was used, with water and methanol (30%: 70%) as the mobile phase, and the flow rate was 1 mL / min. The peak areas of the solution before and after degradation were tested by high performance liquid chromatography, and the ratio of the two was calculated to obtain the degradation rate of HMX.
[0063] like Figure 3As shown, the cathode materials prepared with a molar ratio of Mn to Ce of approximately 1:3 to 3:3 have a good degradation effect on HMX. When the molar ratio of Mn to Ce is 2:3, the degradation effect of the cathode material is optimal.
[0064] Comparative Example 1
[0065] Preparation of CuO NWs / CF: The copper foam was cut into thin slices (1 cm long, 1 cm wide, and 0.1 cm thick), and soaked in acetone, ethanol, and acetic acid for 15 min, respectively, and then washed with deionized water. The activated copper foam was stirred in NaOH and (NH 4 ) 2 S 2 O 8 The mixed solution (prepared with deionized water, NaOH concentration of 2.5 mol / L, (NH 4 ) 2 S 2 O 8 The electrode sheet was taken out with tweezers, and the sample was rinsed with deionized water to remove surface impurities and dried at 60 °C for 10 h. Finally, the sample was heated at a rate of 3 °C·min in air atmosphere. -1 The temperature was raised to 350°C and calcined at 350°C for 2 h to obtain the cathode material, which was recorded as CuO NWs / CF.
[0066] CeO 2 Preparation of @CuO NWs / CF: The copper foam was cut into thin slices (1 cm long, 1 cm wide, and 0.1 cm thick), and soaked in acetone, ethanol, and acetic acid for 15 min, respectively, and then washed with deionized water. At room temperature, the activated copper foam was stirred in NaOH and (NH 4 ) 2 S 2 O 8 The mixed solution (prepared with deionized water, NaOH concentration of 2.5 mol / L, (NH 4 ) 2 S 2 O 8 The concentration was 0.13 mol / L) and then immersed in water for 0.5 h to uniformly grow Cu(OH) on the copper foam. 2 The nanoneedle array was taken out and dried at 60°C for 10 hours to obtain a Cu(OH) 2 Copper foam with nanoneedle arrays. Under slow magnetic stirring, the Cu(OH) 2 The copper foam of the nanoneedle array was immersed in 0.2 mol / L Ce(NO 3 ) 2 6H 2O aqueous solution, react at 80℃ for 1h; transfer the obtained solid to an aqueous solution of 1 mol / L NaOH, react at room temperature for 30 minutes, take out the electrode sheet with tweezers, rinse the sample with deionized water to remove surface impurities, and dry it at 60℃ for 10 hours; finally, in air atmosphere, heat at a rate of 3℃·min -1 The temperature was raised to 350°C and calcined at 350°C for 2 h to obtain the cathode material, which was recorded as CeO 2 @CuO NWs / CF.
[0067] MnO 2 Preparation of @CuO NWs / CF: The copper foam was cut into thin slices (1 cm long, 1 cm wide, and 0.1 cm thick), and soaked in acetone, ethanol, and acetic acid for 15 min, respectively, and then washed with deionized water. At room temperature, the activated copper foam was stirred in NaOH and (NH 4 ) 2 S 2 O 8 The mixed solution (prepared with deionized water, NaOH concentration of 2.5 mol / L, (NH 4 ) 2 S 2 O 8 The concentration was 0.13 mol / L) and then immersed in water for 0.5 h to uniformly grow Cu(OH) on the copper foam. 2 The nanoneedle array was taken out and dried at 60°C for 10 hours to obtain a Cu(OH) 2 Copper foam with nanoneedle arrays. Under slow magnetic stirring, the Cu(OH) 2 The copper foam of the nanoneedle array was immersed in 0.133 mol / L Mn(NO 3 ) 2 ·4H 2 O aqueous solution, react at 80℃ for 1h; transfer the obtained solid to an aqueous solution of 1 mol / L NaOH, react at room temperature for 30 minutes, take out the electrode sheet with tweezers, rinse the sample with deionized water to remove surface impurities, and dry it at 60℃ for 10 hours; finally, in air atmosphere, heat at a rate of 3℃·min -1 The temperature was raised to 350°C and calcined at 350°C for 2 h to obtain the cathode material, which was recorded as MnO 2 @CuO NWs / CF.
[0068] Comparative Example 2
[0069] Referring to Example 1 "Preparation of anode materials", only Co(NO 3 ) 2 6H 2 O was replaced by an equimolar amount of Cd(NO 3 )2 ·4H 2 O, Cu(NO 3 ) 2 ·3H 2 O, Fe(NO 3 ) 3 9H 2 O、Mn(NO 3 ) 2 ·4H 2 O.Ni(NO 3 ) 2 6H 2 O、Zn(NO 3 ) 2 6H 2 O, and the rest are the same as in Example 1 "Preparation of anode materials". The prepared materials are respectively denoted as CdS 2 @CC, CuS 2 @CC, FeS 2 @CC, MnS 2 @CC, NiS 2 @CC, ZnS 2 @CC.
[0070] Example 3
[0071] The inventors used Chenhua 760 electrochemical workstation to test different cathode materials (CuO NWs / CF, CeO 2 @CuONWs / CF、MnO 2 @CuO NWs / CF, CeO 2 -MnO 2 @CuO NWs / CF) and different anode materials (CoS 2 @CC, CdS 2 @CC, CuS 2 @CC, FeS 2 @CC, MnS 2 @CC, NiS 2 @CC, ZnS 2 @CC、)'s electrochemical characteristics ( Figure 4-Figure 5 ). The volt-ampere characteristic curve and impedance curve show that CeO 2 -MnO 2 @CuO NWs / CF and CoS 2 @CC has a larger current area and a smaller curve radius, and has a faster electron transfer ability during the degradation process, which is beneficial to improve the degradation rate of organic pollutants. 2 -MnO 2 @CuO NWs / CF is the cathode material of H electrolyzer, CoS 2@CC is the anode material of the H electrolyzer.
[0072] Testing CeO using an electrochemical workstation 2 -MnO 2 @CuO NWs / CF valence states and conduction bands, and the electron transfer mechanism diagram ( Figure 6 ), electrons are transferred from CuO to CeO 2 -MnO 2 , photogenerated electrons are generated by CeO 2 -MnO 2 Applying an external voltage in the same direction forms an internal electric field, which inhibits the transfer of carriers between the two semiconductors. 2 -MnO 2 The internal electric field of @CuO NWs / CF is opposite to the external voltage, thus improving the interfacial conductivity. With the formation of the space charge layer, strong positive charge active sites appear in the CeO heterojunction due to charge depletion. 2 -MnO 2 side, leading to ROS generation and promoting HMX degradation.
[0073] Example 4
[0074] Based on the results of Example 3, it is determined that CeO 2 -MnO 2 @CuO NWs / CF as cathode, CoS 2 @CC was used as the anode to investigate the electrocatalytic degradation of organic pollutants and the degradation effects of different current densities on HMX and DNAN.
[0075] Investigation of catalytic degradation of organic pollutants:
[0076] Weigh 10 mg HMX into a 1L volumetric flask and titrate to the mark with deionized water to obtain a 10 mg / L HMX solution; weigh 15 mg DNAN into a 1L volumetric flask and titrate to the mark with deionized water to obtain a 15 mg / L DNAN solution; adjust the initial pH of the HMX solution and DNAN solution to 7 with 0.1 mmol / L sulfuric acid and 0.1 mmol / L sodium hydroxide. 2 @CC) as anode (anode area is 1cm 2 ), in the cathode chamber, the cathode material (CeO 2 -MnO 2 @CuO NWs / CF) as cathode (cathode area 1cm 2), the two electrode chambers were separated by N117 proton exchange membrane. 50 mL of HMX solution was placed in the cathode chamber of the H-type electrolyzer, and 50 mL of DNAN solution was placed in the anode chamber of the H-type electrolyzer. At the same time, peroxymonosulfate (2KHSO 5 ·KHSO 4 ·K 2 SO 4 , final concentration 20 mg / L) as an auxiliary activator for the anode material, and the electrolyte in the cathode and anode compartments was 0.05 mol / L Na 2 SO 4 After power on, about 2 mL of solution was taken out from the cathode chamber with a syringe every 10 min, filtered with a 0.22 μm polyethersulfone filter membrane, and quenched with 0.5 mL of methanol to remove the remaining free radicals. About 2 mL of solution was taken out from the cathode chamber with a syringe every 1 min, filtered with a 0.22 μm polyethersulfone filter membrane, and quenched with 0.5 mL of methanol to remove the remaining free radicals. The concentration of HMX was detected at 254 nm using a high performance liquid chromatography (HPLC) UV-visible detector, and the concentration of DNAN was detected at 280 nm. The reverse phase chromatographic column C18 column (5 μm, 4.6 mm × 250 mm) was used, with water and methanol (30%: 70%) as the mobile phase, and the flow rate was 1 mL / min. The peak areas of the solution before and after degradation were tested by high performance liquid chromatography, and the ratio of the two was calculated to obtain the degradation rate.
[0077] from Figure 7 It can be seen that when no current is applied, the degradation of HMX and DNAN is almost 0%. -2 Increase to 10 mA cm -2 When the current density was increased, the total degradation rate of HMX increased from 63.2% to 95.1% after 80 min of reaction. This improvement was attributed to the increased generation of reactive oxygen species with increasing current density. However, further increasing the current resulted in a decrease in the degradation efficiency, presumably due to the excess H 2 O 2 Possibly captures OH to produce O 2 H, O 2 H has a weaker oxidation potential and is less effective in removing organic pollutants. For the anode, without external current, the degradation rate of DNAN was 83.2% after 5 min treatment, which was attributed to the degradation of CoS 2 Activated by PMS ( Figure 7 ); at a current density of 10 mA cm -2 Under the condition of 100 % , the external current further assisted activation, and the removal rate of DNAN increased to 100%. Considering the degradation effects of HEF and AO, the optimal external current density was 10 mA cm -2 .
[0078] Example 5
[0079] The initial pH value of the HMX solution and the initial pH value of the DNAN solution were screened.
[0080] The initial pH of the HMX solution with a concentration of 10 mg / L was adjusted to 3, 5, 7, 9, and 11 using 0.1 mmol / L sulfuric acid and 0.1 mmol / L sodium hydroxide; the initial pH of the DNAN solution with a concentration of 15 mg / L was adjusted to 3, 5, 7, 9, and 11 using 0.1 mmol / L sulfuric acid and 0.1 mmol / L sodium hydroxide.
[0081] Referring to Example 4 "Study on Electrocatalytic Degradation of Organic Pollutants", the initial pH value was used to investigate the degradation effect of 10 mg / L HMX solution and 15 mg / L DNAN solution. Only the initial pH of the HMX solution added to the cathode chamber of the H-type electrolytic cell and the initial pH of the DNAN solution added to the anode chamber of the H-type electrolytic cell were adjusted. The initial pH of the HMX solution added to the cathode chamber of the H-type electrolytic cell and the initial pH of the DNAN solution added to the anode chamber were the same. The applied current density was 10 mA cm -2 , the rest are the same as Example 4 "Investigation of electrocatalytic degradation of organic pollutants".
[0082] from Figure 8 It can be seen that as the pH value changes from weak acid to neutral, the removal rate of HMX (reaction time 80 minutes) increases significantly. Specifically, at pH 3, the removal efficiency is inhibited due to the corrosion of the electrode under strong acid conditions. Under alkaline conditions, H 2 O 2 The consumption of ions increases, further reducing the catalytic efficiency of the electrode.
[0083] from Figure 8 As can be seen in b, when the initial pH is 7-11, the degradation efficiency of DNAN (reaction time 5 minutes) exceeds 90% within 5 minutes. Under acidic conditions, the abundant H + Will be with SO 4 ·- react with HSO 5 - On the other hand, under strong alkaline conditions, PMS mainly forms hydrogen bonds in the form of SO 5 2- In the form of CoS 2 @CC and SO 5 2- The mutual electrostatic repulsion between them will lead to a decrease in the removal rate of DNAN.
[0084] When the initial pH of the cathode chamber is 5 and the initial pH of the anode chamber is 9, the H +The ion balance can be maintained through the N117 proton exchange membrane to the cathode chamber, thereby achieving the maximum efficiency of double degradation.
[0085] Example 6
[0086] Screening of electrolytes (and the effects of anions in the solution on degradation). Referring to Example 4 "Study on electrocatalytic degradation of organic pollutants", different anions (SO 4 2- ,HCO 3 - ,Cl - ,NO 3 - ,HPO 4 - , corresponding to Na 2 SO 4 ,NaHCO 3 ,NaCl,NaNO 3 ,Na 2 HPO 4 The degradation effect of HMX solution with a concentration of 10 mg / L (reaction time 80 minutes) and DNAN solution with a concentration of 15 mg / L (reaction time 5 minutes) was investigated. The initial pH of the HMX solution added to the cathode chamber of the H-type electrolytic cell was adjusted to 5, and the initial pH of the DNAN solution added to the anode chamber of the H-type electrolytic cell was adjusted to 9. The same anion was used as the electrolyte in both the cathode chamber and the anode chamber (the concentration was 0.05 mol / L), and the applied current density was 10 mA cm -2 .
[0087] from Figure 8 c can be seen, SO 4 2- The effect on the degradation of organic pollutants was negligible, and the removal efficiency of DNAN and HMX was almost unaffected. - and HPO 4 2- The effect on degradation is small, and the slight inhibitory effect is caused by their interaction with OH and SO 4 ·- Reaction to form HCO 3 ·, Cl· and HPO 4 ·, which may hinder degradation. It is worth noting that when sodium bicarbonate is used as the electrolyte, it reacts with H + A reaction occurs, which reduces the conductivity of the solution, resulting in a decrease in current density, thereby reducing the degradation rate of DNAN and HMX. 3 - There was no effect on DNAN degradation, but a smaller effect on HMX degradation was shown, which is due to the fact that NO 3 -It is reduced at the cathode to produce additional OH - , which consumes reactive oxygen species in solution and causes competition with HMX degradation.
[0088] Example 7
[0089] Referring to Example 4 "Study on Electrocatalytic Degradation of Organic Pollutants", a 10 mg / L HMX solution and a 15 mg / L DNAN solution were degraded, and only the initial pH of the HMX solution added to the cathode chamber of the H-type electrolytic cell was adjusted to 5, the initial pH of the DNAN solution added to the anode chamber of the H-type electrolytic cell was adjusted to 9, and the electrolyte was 0.05 mol / L Na 2 SO 4 , the applied current density is 10 mA cm -2 Electron paramagnetic resonance (EPR) was used to test the types of reactive oxygen species produced by the cathode and anode during the degradation process ( Fig. 9 ), the result is as follows Figure 10-11 shown.
[0090] To investigate the reactive oxygen species generated during cathode degradation, 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) was used as a capture agent, and the characteristic peaks of DMPO-H* and the weak 1:2:2:1 response of DMPO-·OH were recorded ( Fig.10 a), confirming the formation of atomic H* and ·OH. 2 · - The signal of the adduct was not captured, which may be due to its easy conversion into 1 O 2 ( Fig.10 c). Fig.10 b The free radical signals at different time points were recorded, indicating that free radicals were continuously generated during the entire degradation process.
[0091] To investigate the reactive oxygen species generated during the anode degradation process, such as Fig.11 As shown in a, all relevant reactive oxygen species (·OH, O 2 · - and SO 4 ·- and can be captured in EPR. Fig.11 Tetramethylpiperidinyl oxide (TEMP) can be observed in b, and TEMP- 1 O 2 The strong signal peak of the adduct indicates that AO is generated during the reaction. 1 O 2 .
[0092] Example 8
[0093] The electron-deficient organic pollutants cyclotrimethylene trinitramine and hexanitrohexaazaisowurtzitane were taken, and cyclotrimethylene trinitramine (RDX, concentration of 20 mg / L) solution and hexanitrohexaazaisowurtzitane (CL-20, concentration of 6 mg / L) solution were prepared with deionized water, and the initial pH of cyclotrimethylene trinitramine solution and hexanitrohexaazaisowurtzitane solution were adjusted to 5 with 0.1 mmol / L sulfuric acid and 0.1 mmol / L sodium hydroxide. When the pollutant in the anode chamber is DNAN (concentration of 15 mg / L) aqueous solution, the cyclotrimethylene trinitramine solution or hexanitrohexaazaisowurtzitane solution was added as a single solution to the cathode chamber of the H-type electrolytic cell to form a combination, and the cathode reaction time was 80 minutes and the anode reaction time was 9 minutes.
[0094] The electron-rich organic pollutants trinitrotoluene, disodium tetrazolyl azolide, 3-nitro-1,2,4-triazol-5-one and nitroguanidine were prepared with deionized water to prepare trinitrotoluene (TNT, concentration of 15 mg / L) solution, disodium tetrazolyl azolide (Na 2 AzTz, concentration of 20 mg / L) solution, 3-nitro-1,2,4-triazol-5-one (NTO, concentration of 30 mg / L) solution, nitroguanidine (NQ, concentration of 60 mg / L) solution, 0.1 mmol / L sulfuric acid and 0.1 mmol / L sodium hydroxide were used to adjust the initial pH of trinitrotoluene solution, disodium azotetrazolyl solution, 3-nitro-1,2,4-triazol-5-one solution, and nitroguanidine solution to 9. When the cathode chamber pollutant is HMX (concentration of 10 mg / L) solution, trinitrotoluene solution, disodium azotetrazolyl solution, 3-nitro-1,2,4-triazol-5-one solution or nitroguanidine solution is added to the anode chamber of the H-type electrolytic cell as a single solution to form a combination, the cathode reaction time is 80 minutes, and the anode reaction time is 9 minutes.
[0095] Referring to Example 4 "Study on Electrocatalytic Degradation of Organic Pollutants", only the pollutants in the cathode chamber or the anode chamber were adjusted to investigate the anode material (CoS 2 @CC) as anode, cathode material (CeO 2 -MnO 2 @CuO NWs / CF) as cathode (cathode and anode areas are both 1 cm 2 , the initial pH of the cathode chamber is 5, the initial pH of the anode chamber is 9, and the electrolytes of the cathode and anode chambers are both 0.05 mol / L SO 4 2- , current density 10mA·cm -2 )Degradation effect on different organic pollutants.
[0096] The experimental results are as follows Fig.12As shown, within 2 hours, the degradation rates of cyclotrimethylene trinitramine and hexanitrohexaazaisowurtzitane reached 95.3% and 81.1%, respectively, and the total organic carbon (TOC) removal rates were 66.7% and 41.1%, respectively. Within 9 minutes, the total organic carbon removal rates of trinitrotoluene, disodium azotetrazolyl, 3-nitro-1,2,4-triazol-5-one, and nitroguanidine were 68%, 81%, 56%, and 73%, respectively, indicating that the cathode material and anode material of the present invention have good applicability in treating typical wastewater lacking / rich in explosives.
[0097] Example 9
[0098] Referring to Example 4 "Investigation of electrocatalytic degradation of organic pollutants", the ability of cathode materials and anode materials to catalyze the degradation of HMX solution (10 mg / L) and DNAN solution (15 mg / L) was tested. The cathode was degraded for 80 minutes and the anode was degraded for 9 minutes. After the degradation was completed, the electrode material was removed and rinsed with deionized water. The electrode material was placed in an oven at 80°C for 3 hours to be dried. The catalyst was recovered and the degradation of HMX solution (10 mg / L) and DNAN solution (15 mg / L) was continued. The electrode material recovered for the fifth time degraded HMX solution (10 mg / L) and DNAN solution (15 mg / L) by 90.2% and 92.5%, respectively, indicating that CeO 2 -MnO 2 @CuONWs / CF and CoS 2 @CC has excellent cyclability and stability. The stability ensures that no sludge falls while achieving a high degradation rate.
Claims
1. An electrode material for an H-type electrolytic cell, comprising a cathode material and an anode material, characterized in that: The cathode material is prepared by immersing copper foam in a mixed aqueous solution of NaOH and ammonium persulfate to obtain copper foam with a Cu(OH)2 nanoneedle array, then immersing the copper foam with the Cu(OH)2 nanoneedle array in a Mn(NO3)2·4H2O aqueous solution for reaction, then adding Ce(NO3)2·6H2O to continue the reaction, then transferring to a NaOH aqueous solution for treatment, drying, and obtaining a cathode material precursor, and then calcining the cathode material precursor in an air atmosphere to obtain a cathode material; The anode material is prepared by adding Co(NO3)2·6H2O and polyvinyl pyrrolidone into a mixed solvent of water and ethylene glycol, and then adding sodium thiosulfate to react to obtain a precursor liquid, placing an activated carbon fiber cloth into the precursor liquid, heat treating it at 140-160°C for 10-12 hours, cooling it to room temperature, taking out the activated carbon fiber cloth, washing it with deionized water, and drying it to obtain the anode material.
2. The electrode material for an H-type electrolytic cell according to claim 1, characterized in that: The cathode material is prepared by the following method: at room temperature, immersing activated copper foam in a mixed aqueous solution of NaOH and ammonium persulfate for 0.5 to 1 hour to obtain copper foam with a Cu(OH)2 nanoneedle array; immersing the copper foam with the Cu(OH)2 nanoneedle array in a Mn(NO3)2·4H2O aqueous solution, reacting at 70 to 85°C for 0.8 to 1.2 hours, then adding Ce(NO3)2·6H2O, reacting at 70 to 85°C for 0.8 to 1.2 hours, transferring the copper foam to a NaOH aqueous solution, soaking at room temperature for 30 to 40 minutes, taking out the copper foam, rinsing with deionized water, and drying to obtain a cathode material precursor; calcining the cathode material precursor at 300 to 350°C in an air atmosphere for 2 to 2.5 hours to obtain the cathode material.
3. The electrode material for an H-type electrolytic cell according to claim 1 or 2, characterized in that: In the mixed aqueous solution of NaOH and ammonium persulfate, the concentration of NaOH is 2-2.5 mol / L, and the concentration of ammonium persulfate is 0.10-0.16 mol / L.
4. The electrode material for an H-type electrolytic cell according to claim 1 or 2, characterized in that: The concentration of the Mn(NO3)2·4H2O aqueous solution is 0.1-0.166 mol / L; the molar ratio of Mn(NO3)2·4H2O to Ce(NO3)2·6H2O is 1:3-3:3, preferably 2:
3.
5. The electrode material for an H-type electrolytic cell according to claim 1, characterized in that: The anode material is prepared by the following method: adding Co(NO3)2·6H2O and polyvinyl pyrrolidone to a mixed solvent of ethylene glycol, mixing evenly, adding sodium thiosulfate, reacting at room temperature for 1.5 to 2 hours, ultrasonically treating for 30 to 40 minutes to obtain a dispersion; immersing an activated carbon fiber cloth in the dispersion, heat treating at 140 to 160°C for 12 hours, taking out the activated carbon fiber cloth, washing it with deionized water, and drying it at 50 to 70°C for 8 to 12 hours to obtain the anode material.
6. The electrode material for an H-type electrolytic cell according to claim 1 or 2, characterized in that: The mass ratio of the Co(NO3)2·6H2O and polyvinyl pyrrolidone is 0.95:1 to 1:1; the dosage ratio of the Co(NO3)2·6H2O and water is 1:30 to 1:35 g / mL; the volume ratio of water to ethylene glycol is 1:1; the molar ratio of the Co(NO3)2·6H2O and sodium thiosulfate is 0.5:1 to 0.55:
1.
7. A method for simultaneously degrading typical explosive-deficient / explosive-rich wastewater, characterized in that: include: An H-type electrolytic cell is used, a cathode chamber and an anode chamber are separated by a proton membrane, an electron-deficient organic pollutant aqueous solution is added to the cathode chamber, an electron-rich organic pollutant aqueous solution and peroxymonosulfate are added to the anode chamber, and the cathode material and the anode material according to claim 1 are used as the cathode and the anode, respectively, and SO4 2- 、HCO3 - , Cl - 、NO3 - or HPO4 2- It is an electrolyte that can simultaneously degrade electron-deficient organic pollutants and electron-rich organic pollutants under the action of an external current.
8. The method for simultaneously degrading typical explosive-deficient / explosive-rich wastewater according to claim 7, characterized in that: The area of the cathode is 1 cm 2 The area of the anode is 1cm 2 ; The applied current density is 5 to 20 mA, preferably 10 to 15 mA, and most preferably 10 mA.
9. The method for simultaneously degrading typical wastewater lacking / rich in explosives according to claim 7, characterized in that: The initial pH of the aqueous solution of electron-deficient organic pollutants in the cathode chamber is 3 to 11, preferably 5 to 7, and more preferably 5; the initial pH of the aqueous solution of electron-rich organic pollutants in the anode chamber is 3 to 11, preferably 7 to 11, and more preferably 9; The final concentration of the peroxymonosulfate is 20-25 mg / L; the concentration of the electrolyte is 0.050-0.055 mol / L; The electrolyte is SO4 2- or NO3 - , preferably SO4 2- .
10. The method for simultaneously degrading typical wastewater lacking / rich in explosives according to claim 7, characterized in that: The concentration of the electron-deficient organic pollutant aqueous solution is 6 to 20 mg / L, and the concentration of the electron-rich organic pollutant aqueous solution is 10 to 60 mg / L; The electron-deficient organic pollutant is at least one of tetramethylene tetranitramine, cyclotrimethylene trinitramine and hexanitrohexaazaisowurtzitane; the electron-rich organic pollutant is at least one of trinitrotoluene, disodium azotetrazolyl, 3-nitro-1,2,4-triazole-5-one and nitroguanidine.
Citation Information
Patent Citations
Porous NiO / CeO2 hybrid nanosheet array, and preparation method and application thereof
CN104649337A
Nano-copper array cathode for reductive degradation of organic pollutants as well as preparation and application thereof
CN107244717A
Carbon-coated mesoporous transition metal sulfide negative electrode material as well as preparation method and application thereof
CN112768656A
Preparation method and application of self-supporting copper-based composite metal nanosheet array electrode material
CN116332294A
Carrier supporting metal fine particle colloid, carrier supporting platinum group containing colloid, carrier supporting palladium colloid, carrier supporting platinum colloid, carrier supporting palladium-platinum alloy fine particle colloid, carrier supporting palladium-platinum core-shell fine particle colloid, and high concentration continuous manufacturing method thereof and catalyst, sensor, battery, Anti-bacteria material
JP2021142469A
Cited By
Method and system for degrading RDX wastewater by microbial fuel cell
CN120573846A